2006
DOI: 10.1088/0026-1394/43/5/012
|View full text |Cite
|
Sign up to set email alerts
|

Set standard deviation, repeatability and offset of absolute gravimeter A10-008

Abstract: The set standard deviation, repeatability and offset of absolute gravimeter A10-008 were assessed at the Walferdange Underground Laboratory for Geodynamics (WULG) in Luxembourg. Analysis of the data indicates that the instrument performed within the specifications of the manufacturer. For A10-008, the average set standard deviation was (1.6 ± 0.6) µGal (1Gal ≡ 1 cm s−2), the average repeatability was (2.9 ± 1.5) µGal, and the average offset compared to absolute gravimeter FG5-216 was (3.2 ± 3.5) µGal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…In the last decade, formalized comparisons of absolute gravimeters have been conducted only in Europe at the Bureau International des Poids et Mesures (BIPM) and the Underground Laboratory for Geodynamics in Walferdange (WULG) (Vitushkin et al 2002;Francis and van Dam 2006;Francis et al 2010;Jiang et al 2011); these comparisons were well organized with more than 10 gravimeters participating. Smaller comparisons of two absolute gravimeters have often occurred in the last decade, and they have often been performed in other smaller observatories; these smaller comparisons also were primarily performed in Europe, but the Canadian Absolute Gravity Site (CAGS) in Canada was also utilized (Liard et al 2003;Van Camp et al 2003;Schmerge and Francis 2006;Simon et al 2006;Wilmes and Falk 2006). On October 18, 2010, participants of the 2010 North American Comparison of Absolute Gravimeters (NACAG-2010) met at the David Skaggs Research Center in Boulder, Colorado for a one day workshop to discuss topics concerning absolute gravity.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, formalized comparisons of absolute gravimeters have been conducted only in Europe at the Bureau International des Poids et Mesures (BIPM) and the Underground Laboratory for Geodynamics in Walferdange (WULG) (Vitushkin et al 2002;Francis and van Dam 2006;Francis et al 2010;Jiang et al 2011); these comparisons were well organized with more than 10 gravimeters participating. Smaller comparisons of two absolute gravimeters have often occurred in the last decade, and they have often been performed in other smaller observatories; these smaller comparisons also were primarily performed in Europe, but the Canadian Absolute Gravity Site (CAGS) in Canada was also utilized (Liard et al 2003;Van Camp et al 2003;Schmerge and Francis 2006;Simon et al 2006;Wilmes and Falk 2006). On October 18, 2010, participants of the 2010 North American Comparison of Absolute Gravimeters (NACAG-2010) met at the David Skaggs Research Center in Boulder, Colorado for a one day workshop to discuss topics concerning absolute gravity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MGL announced the accuracy of A10 is 10 gal, which is restricted by numerous factors including the tides and other geophysical corrections. [25] investigated and discussed about the precision and the accuracy of A10-008 and they confirmed that it was better performance than the specifications. As described later, we also confirmed that the accuracy of A10-017 usually shows better than 10 gal in good condition.…”
Section: Absolute Gravity Measurements Using the A10 Gravimetermentioning
confidence: 84%
“…Although nominal accuracy for the A-10 absolute gravimeter reported by the manufacturer is ±10 microGal (1 microGal = 1x10 -8 m/s 2 ), after several years of operation, the observational standard deviation for measurements using a single gravimeter at stable sites is estimated to be ±5 microGal, and this value is used in data processing (Schmerge and Francis, 2006;Kennedy and Winester, 2011). To ensure this accuracy is met, the instrument undergoes periodic calibration, maintenance, and comparison with other absolute gravimeters (Schmerge and Francis, 2006;Schmerge and others, 2012). Earth tide corrections for absolute gravity measurements are determined using the ETGTAB model with the default wave groups in the Micro-g Lacoste, Inc. software (http://www.microglacoste.com/).…”
Section: Absolute Gravity Measurementsmentioning
confidence: 99%